Penghalang Pernikahan (Rabaib) - Andriani, Rizky; Yanti, Helmida; Amar Adly, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Tafsir scholars do not question the indecency of women who are haram married for reasons of heredity or breast milk. However, regarding women It is forbidden to marry for reasons of marriage, then this is where there is a difference of opinion Mufasir in understanding or interpreting the lawfulness of unlawful women.Married by a man for marital reasons. As is known, women who are forbidden are married for reasons The marriage of one of them is a stepchild, so differences of opinion are mutually exclusive understand about the unlawfulness of women who are forbidden to marry for reasons of marriage Namely, it is found in the understanding of the stepchildren. Based on the description above, the author wants to study it in depth “Barriers to Rabaib Marriage.